Design and Testing of a New Piezoelectric-Actuated Symmetric Compliant Microgripper - Zekui Lyu; Qingsong Xu (Actuators, 2022)
Precise and stable operations in micromanipulation and microassembly require a high-performance microgripper. To improve the predominant static and dynamic characteristics, a novel piezoelectric-actuated compliant microgripper is designed, analyzed, and tested in this paper. The microgripper realizes a large gripping stroke by integrating a compliant bridge mechanism, an L-shaped mechanism, and a levered parallelogram mechanism. Optimization technology based on response surface analysis is applied to demonstrate the influence of structural parameters on the microgripper performance. Simulation results of finite element analysis reveal the superior performance of the designed microgripper in terms of gripping displacement, mechanism stiffness, equivalent stress, and natural frequency. A gripper prototype has been fabricated, and experimental studies have been conducted to test the microgripper’s physical properties. Experimental results show that the microgripper can grasp micro-objects with a maximum jaw motion stroke of 312.8 <semantics>μ</semantics>m, natural frequency of 786 Hz, motion resolution of ±0.6 <semantics>μ</semantics>m, and force resolution of ±1.69 mN. The gripping tests of an optical fiber with a diameter of 200 <semantics>μ</semantics>m and a metal sheet with a thickness of 100 <semantics>μ</semantics>m have been performed to demonstrate its gripping capability with position and force control.